Exploring digital competencies in higher education: design and validation of instruments for the era of Industry 5.0 - Pelaez-Sanchez, Iris Cristina; Glasserman-Morales, Leonardo David; Rocha-Feregrino, Gerardo (Frontiers in Education, 2024)
Industry 5.0 is the next phase of industrial work that integrates robots and artificial intelligence to boost productivity and economic growth. It emphasizes a balance between human creativity and technological precision, built on three pillars: human centrality, sustainability, and resilience. Corporations and educational institutions must adopt an integrated approach to training their future workforce, emphasizing digital and key competencies such as creativity, communication, collaboration, and critical thinking. Higher education institutions must measure digital competencies and other key Industry 5.0 competencies to prepare students for a sustainable future. However, there is a need to identify appropriate scientific instruments that can comprehensively evaluate these competencies. This study conducted a Systematic Literature Review to analyze the existing digital competency assessment instruments in higher education from 2013-2023. Within the reviewed literature, surveys and questionnaires emerged as the predominant methods utilized for this purpose. The focus was on instruments that measure digital competencies and core competencies for Industry 5.0, such as creativity, communication, collaboration, and critical thinking. The search process began with a strategy applied across various databases, including ERIC, Google Scholar, ProQuest, Scopus, and Web of Science, to cover a broad range of literature on the design and validation of digital competency assessment tools. This search generated a total of 9,563 academic papers. Inclusion, exclusion, and quality filters were applied to select 112 articles for detailed analysis. Among these 112 articles, 46 focused on designing and validating digital competency assessment instruments in higher education. This study found a direct relationship between digital competencies and essential skills like communication and critical thinking. Assessment instruments should cover a broader range of competencies, including creativity and collaboration, to meet the demands of Industry 5.0. Reliable assessments of digital competencies and soft skills are crucial, with a need for appropriate reliability tests that do not impact students' preparedness for labor market challenges. The study concludes that assessment tools should integrate a wide range of competencies, and students and educators should be actively involved in developing these skills. Future research should focus on designing tools that effectively evaluate these competencies in dynamic work contexts.